Quantitative analysis of the formation mechanism of tightly bound rubber by using carbon-coated alumina nanoparticles as a model filler. (March 2021) - Hoshikawa, Yasuto; Kawaguchi, Rei; Nomura, Keita; Akahane, Hidenobu; Ishii, Takafumi; Ando, Mariko; Hoshino, Norihisa; Akutagawa, Tomoyuki; Yamada, Hiroshi; Kyotani, Takashi
Abstract: Using carbon-coated alumina nanoparticles as a model filler for styrene-butadiene rubber (SBR), rubber composites with different carbon surface chemistry were prepared and the bound rubber thus formed in each composite was analyzed in relation to the carbon surface chemistry. The present approach provides quantitative understanding of the rubber-carbon interface at the molecular level and thereby the formation mechanism of tightly bound rubber during a mixing process with SBR is proposed as follows. At first, the strong physisorption of SBR occurs and almost all the filler surface (99.8% of the total surface) is covered with a single-molecule layer of physisorbed SBR. The polymer radicals formed in the process are then gradually allowed to react with the H-terminated edge sites on the exposed carbon surface (0.2% of the total surface) and the resulting free edge sites are chemically-bonded to the other polymer radicals to form the chemisorbed polymer. Moreover, the unique structure of the present composites makes it possible to analyze the state of tightly bound rubber with the conventional differential scanning calorimetry, which strongly suggests that the tightly bound rubber is indeed in a glassy state. Graphical abstract: Image 1